Financial Accounting Software Application for MSME Members of Baitul Maal Wat Tamwil (BMT) in South Sumatra - Soediro, Achmad; Kusumawardani, Media; Farhan, Muhammad; Adhitama, Fardinant; Yusrianti, Hasni (Sricommerce: Journal of Sriwijaya Community Services, 2024)
Implementation of Community Service Activities with the theme "Creation and Training of Financial Accounting Software Applications for Members of Baitul Maal wat Tamwil (BMT) Micro, Small, and Medium Enterprises (MSMEs) in South Sumatra." This community service activity received positive responses from participants, as evidenced by evaluations submitted through a Google Form. The favorable responses regarding the community service activity can be broadly categorized into at least two aspects: firstly, the activity effectively enhanced participants' knowledge, and secondly, the presenters demonstrated a strong command of the delivered content. Several participants recommended conducting similar activities periodically, with a focus on delving deeper into specific topics.